The repeat region of the circumsporozoite protein is critical for sporozoite formation and maturation in Plasmodium - Ferguson, D; Balaban, A; Patzewitz, E; Wall, R; Hopp, C; Poulin, B; Mohmmed, A; Malhotra, P; Coppi, A; Sinnis, P; Tewari, R (Public Library of Science, 2014)
The circumsporozoite protein (CSP) is the major surface protein of the sporozoite stage of malaria parasites and has multiple functions as the parasite develops and then migrates from the mosquito midgut to the mammalian liver. The overall structure of CSP is conserved among Plasmodium species, consisting of a species-specific central tandem repeat region flanked by two conserved domains: the NH2-terminus and the thrombospondin repeat (TSR) at the COOH-terminus. Although the central repeat region is an immunodominant B-cell epitope and the basis of the only candidate malaria vaccine in Phase III clinical trials, little is known about its functional role(s). We used the rodent malaria model Plasmodium berghei to investigate the role of the CSP tandem repeat region during sporozoite development. Here we describe two mutant parasite lines, one lacking the tandem repeat region (ΔRep) and the other lacking the NH2-terminus as well as the repeat region (ΔNΔRep). We show that in both mutant lines oocyst formation is unaffected but sporozoite development is defective.